2015
DOI: 10.1002/adma.201404900
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Quantum Confinement in Ultrathin, Optically Active Semiconductor Nanowires Via Reverse‐Reaction Growth

Abstract: A unique growth scheme is demonstrated to realize ultrathin GaAs nanowires on Si with sizes down to the sub-10 nm regime. While this scheme preserves the bulk-like crystal properties, correlated optical experiments reveal huge blueshifted photo-luminescence (up to ≈100 meV) with decreasing nanowire cross-section, demonstrating very strong quantum confinement effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 45 publications
(73 reference statements)
11
87
0
Order By: Relevance
“…No significant change in diameter of the wires is observed as a function of the annealing time. This confirms that evaporation occurs mostly from the top facet and is negligible on the side facets, as opposed to what is observed in GaAs [37]. The droplets are located on the corner between two {1-10} facets and stay close to the tip of the nanowire as shown in the 3D schematic in figure 1(d).…”
Section: Resultssupporting
confidence: 66%
“…No significant change in diameter of the wires is observed as a function of the annealing time. This confirms that evaporation occurs mostly from the top facet and is negligible on the side facets, as opposed to what is observed in GaAs [37]. The droplets are located on the corner between two {1-10} facets and stay close to the tip of the nanowire as shown in the 3D schematic in figure 1(d).…”
Section: Resultssupporting
confidence: 66%
“…1(b), with the radius R and thickness L varying within a parameter space enabled by state-ofthe-art fabrication, which includes the regime of quantum confinement in the radial direction. 9,10 One can see that the ground state has almost exclusive HH character except for very thin radii, R < 5 nm. In this region, the ground state rapidly switches from mainly F band (HH) to mainly λ band character, as shown in Fig.…”
Section: B Holesmentioning
confidence: 97%
“…In particular, we assess the validity of the usual assumption that the ground state has a well defined, single-band, HH character. [9][10][11] The eigenfunctions of Hamiltonian H 6B h are sixcomponent spinors of the form: Ψ 6B h = 6 i=1 f i (r)|u i , where f i (r) is the envelope function associated with the |u i Bloch function. The weight of an individual component is computed as |f i | 2 .…”
Section: B Holesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Vainorius et al [159] have reported the synthesis of GaAs polytype QDs with exact control on the dot thickness, while Loitsch et al [170] have grown samples of the same system with various nanowire diameters down to 7 nm. Together, these experimental works show that precise tailoring of the QD geometry and, thus, of the energy structure is possible, which represents the first step towards the development of real devices.…”
Section: Spontaneous Polarization In Gaas Polytype Qdsmentioning
confidence: 99%